Determination of organochlorine pesticides in agricultural soils applyng Quechers, C-ECD and GC-MS/MS - Sá, Luísa Correia (2019)
The organochlorine pesticides (OCPs), due the wide use in agriculture until about 30 years (except the most recent bans by the EU for lindane, methoxychlor and endosulfan) and their chemical stability and slow biodegradation became ubiquitous pollutants. Most OCPs are persistent organic pollutants that have long life cycles in the environment and being transported for long distances. The residues of pesticides in soil can be absorbed by plants, entering the food chain, leading to bioaccumulation. The objective of this study was to determine the presence of 14 OCPs (HCH (α, β, ζ), HCB, lindane, aldrin, α-endosulfan, dieldrin, p, p'-DDE, endrin, endosulfan β-p-p' -DDD, o-p'-DDT and methoxychlor) in soils of 5 Portuguese regions. The extraction was performed with QuEChERS, analysis by GC-ECD and confirmation by GC-MS/MS. One sample showed a residue above the LOQ, revealing contamination by dieldrin at a concentration of 45.36 µg .kg-1.